The role of BioBlitzes in citizen science: insights from participants and experts - Tiago, P.; Evaristo, I.; Pinto, B. (Frontiers in Environmental Science, 2024)
Beyond its primary role in generating scientific knowledge, citizen science also carries a potent educational dimension. An example of citizen science activities is BioBlitzes, collaborative events that bring together both experts and citizens, all united by a common mission: to register species observations within a defined geographic area during a predetermined time frame. In addition to comprehensively characterizing BioBlitz participants across sociodemographic, emotional, and cognitive domains, this study seeks to gain insights into the overall perceptions held by BioBlitz experts regarding these events and their participants. By considering both perspectives, we strive to achieve a more holistic understanding of BioBlitzes, elucidating their significance and impact on both the individuals participating and the broader scientific community involved. The analysed sample corresponded to 96 participants and 11 experts. The evaluation of made by the 96 participants was carried out by applying a pre-questionnaire and post-questionnaire which allowed us to conclude that the participants, in the short term, acquired some knowledge during the event, but few emotional changes were detected. The evaluation of made by the 11 experts was carried out in two online focus group sessions. It was concluded that there is a general opinion that citizens and experts learn during a BioBlitz, appreciate the social dimension of these experiences, and that citizens leave the BioBlitz more aware of nature conservation issues.